Principles of Justice and Riba-Free Practice in Islamic Financial Management - Hasmawati Hasmawati (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
Islamic financial management is grounded in ethical principles that aim to promote social justice, economic balance, and moral accountability. Central to its framework are the principles of justice (al-‘adl) and the prohibition of riba (usury or interest), which serve as pillars in ensuring fairness and equity in financial transactions. The principle of justice emphasizes transparency, mutual consent, and the protection of all parties involved, particularly the economically vulnerable. At the same time, the prohibition of riba aims to eliminate exploitative practices that lead to wealth accumulation without real economic activity, thereby preserving the integrity of wealth distribution in society. These principles align with the broader objectives of Maqasid al-Shariah, which seek to safeguard faith, life, intellect, lineage, and wealth. In practice, Islamic financial management encourages profit-and-loss sharing arrangements, asset-backed financing, and ethical investment strategies that reflect the spirit of inclusivity and sustainability. This abstract explores how justice and the riba-free ethos are implemented in various financial instruments, institutions, and personal finance practices within the Islamic economic system. Ultimately, it highlights the relevance and potential of Islamic finance as a just alternative to conventional models, particularly in addressing inequality and fostering a more ethical global financial order.